RSM and Fuzzy logic approaches for predicting the surface roughness during EDM of Al-SiCp MMC. (2017) - Bhuyan, R.K.; Mohanty, Shalini; Routara, B.C.
Abstract: Surface roughness is the one of the critical performance parameter that has been effect on several mechanical properties of machined parts like friction, wear, light reflection, heat transmission, lubrication, electrical conductivity, etc. Hence this paper present the surface roughness like Ra, Rq and Rz of Al-SiCp metal matrix composite (MMC) during electric discharge machining (EDM). In order to achieved the desired surface roughness the experiment has been planed based on central composite design (CCD) method with three EDM parameters such as pulse-on time (TON ), peak current (Ip ), and flushing pressure (Fp ). In this paper describes the mathematical modeling for response surface methodology (RSM) and fuzzy logic modeling technique to prediction themeasuring surface roughness (Ra, Rz and Rq ) of Al-SiCp metal matrix composite (MMC).Also the performance of the experimental result is compared with the developed fuzzy models and RSM mathematical models and it clearly indicates that the Fuzzy models provide more accurate prediction in compared to the RSM models. Finally the Analysis of Variance (ANOVA) technique is carried out to check the significance of the models and study the effect of process parameters.